Intestinal Bacteroides sp. Imbalance Associated With the Occurrence of Childhood Undernutrition in China - Li, Dongfang; Li, Yinhu; Dai, Wenkui; Wang, Huihui; Qiu, Chuangzhao; Feng, Su; Zhou, Qian; Wang, Wenjian; Feng, Xin; Yao, Kaihu; Liu, Yanhong; Yang, Yonghong; et al. (Frontiers in Microbiology, 2019)
Undernutrition (UN) is a worldwide concern affecting the morbidity and mortality among children while the safety and long-term efficacy of the current treatments remain controversial. Recent evidences showing the roles of gut microbiome (GM) in nutrient absorption enables an alternative intervention to safely treat UN with sustainable amelioration. To enhance our understanding on GM and childhood undernutrition, we deep sequenced the gut metagenomes of 65 children with moderate or severe undernutrition (UN group) and 61 healthy children (HC group) to identify associated taxa and genes using a two-stage validation scheme. At stage I, 54 UN patients and 51 healthy children were enrolled for the discovery of GM markers in UN children. Then, the accuracy of the markers were testified in additional 11 UN patients and 10 healthy children at stage II. Compared to the HC group, the UN group harbored lower richness of microbial genes (P=0.005, FDR=0.005) and species (P=0.002, FDR=0.002). The distributions of bacterial genes enables the identification of 16 gene markers to discriminate the UN patients with high accuracy (averaged areas under receiver operating curve (AUC)=0.87), including three Bacteroides uniformis genes that are responsible for the synthesis of iron transporters. We also identified four species markers to confidently discriminate the UN patients from the HC children (averaged AUC=0.91), including Bacteroides ovatus, Bacteroides uniformis, Bacteroides uniformis and Bacteroides vulgatus. In addition, metabolic comparison showed significantly decreased isobutyric acid (P=0.005, FDR=0.017) and increased isovaleric acid (P=0.006, FDR=0.017) in UN patients. We also identified notable correlations between microbial species and short-chain fatty acids (SCFAs) and several nutritional indicators, including acetic acid and iron (r=0.436, P=0.029), butyric acid and iron (r=0.422, P=0.036), butyric acid and lymphocyte (r=-0.309, P=0.011), acetic acid and total protein (r=-0.303, P=0.043). Taken together, the distinct features of gut microbiota in UN patients highlight the taxonomic and functional shift during the development of UN and provide solid theoretical basis for intervention in childhood undernutrition through gut microbes.